Clinical characteristics predicting early clinical failure after 72 h of antibiotic treatment in women with community‐onset acute pyelonephritis: a prospective multicentre study. (22nd January 2014) - Wie, S.‐H.; Ki, M.; Kim, J.; Cho, Y. K.; Lim, S.‐K.; Lee, J. S.; Kwon, K. T.; Lee, H.; Cheong, H. J.; Park, D. W.; Ryu, S. Y.; Chung, M.‐H.; et al.
Abstract In patients with community‐onset acute pyelonephritis (CO‐APN), assessing the risk factors for poor clinical response after 72 h of antibiotic treatment (early clinical failure) is important. The objectives of this study were to define those risk factors, and to assess whether early clinical failure influences mortality and treatment outcomes. We prospectively collected the clinical and microbiological data of women with CO‐APN in South Korea from March 2010 to February 2012. The numbers of cases in the early clinical success and early clinical failure groups were 840 (79.1%) and 222 (20.9%), respectively. Final clinical failure and mortality were higher in the early clinical failure group than in the early clinical success group (14.9% vs 2.3%, p <0.001; 6.8% vs 0.1%, p 0.001, respectively). In a multiple logistic regression model, the risk factors for early clinical failure among the total 1062 patients were diabetes mellitus (OR 1.5; 95% CI 1.1–2.1), chronic liver diseases (OR 3.3; 95% CI 1.6–6.7), malignancy (OR 2.2; 95% CI 1.1–4.4), Pitt score ≥2 (OR 2.5; 95% CI 1.6–3.8), presence of azotaemia (OR 1.8; 95% CI 1.2–2.7), white blood cell count ≥20 000/mm3 (OR 2.5; 95% CI 1.6–4.0), serum C‐reactive protein level ≥20 mg/dL (OR 1.7; 95% CI 1.2–2.4), and history of antibiotic usage within the previous year (OR 1.5; 95% CI 1.1–2.2). Analysing the subgroup of 743 patients with CO‐APN due to Enterobacteriaceae, fluoroquinolone resistance of the uropathogen was another factor associated with early clinical failure (OR 1.7; 95% CI 1.1–2.5). Simple variables of underlying diseases, previous antibiotic usage and initial laboratory test outcomes can be used to decide on the direction of treatment in CO‐APN.